Feedback for Learning in Pharmacy Education: A Scoping Review - Nicholas R. Nelson; Rebecca B. Carlson; Amanda H. Corbett; Dennis M. Williams; Denise H. Rhoney (MDPI AG, 2021)
Feedback is an effective pedagogy aimed to create cognitive dissonance and reinforce learning as a key component of clinical training programs. Pharmacy learners receive constant feedback. However, there is limited understanding of how feedback is utilized in pharmacy education. This scoping review sought to summarize the breadth and depth of the use of feedback within pharmacy education and identify areas for future research. PubMed, Embase, Scopus, and Web of Science were searched for English articles since January 2000 to identify studies related to feedback in pharmacy education. Sixty-four articles were included for analysis, stratified by moderate and major theory talk, where moderate theory talk explicitly included feedback into study design and major theory talk included feedback into both study design and analysis. Feedback was provided in Bachelor (14%), Master (15.6%), Doctor of Pharmacy (67.2%) and post-graduate programs (4.7%) on a variety of curricular objectives including communication and patient work up in didactic, objective structured clinical examination (OSCE), and experiential settings, and career/interview preparation in the co-curriculum. Feedback comments were mostly written in didactic courses, and both written and verbal in OSCE, experiential, and co-curricular settings. The pharmacy education feedback literature lacks depth beyond student perceptions, especially with respect to assessing the effectiveness and quality of feedback for learning. While feedback has been utilized throughout pharmacy education across myriad outcomes, several areas for inquiry exist which can inform the design of faculty and preceptor development programs, ensuring provision of effective, quality feedback to pharmacy learners.